Surface, interface and electronic properties of F8:F8BT polymeric thin films used for organic light‐emitting diode applications - Borges, Bruno GAL; Veiga, Amanda G; Gioti, Maria; Laskarakis, Argiris; Tzounis, Lazaros; Logothetidis, Stergios; Rocco, Maria Luiza M (Polymer international, 2018)
Ultrathin polymeric films consisting of poly(9,9‐di‐n‐octylfluorenyl‐2,7‐diyl) (F8) blended with poly(9,9‐dioctylfluorene‐alt‐benzothiadiazole) (F8BT) grown onto PEDOT:PSS/ITO/PET were investigated by X‐ray photoelectron spectroscopy (XPS), depth‐profiling XPS, reflection electron energy loss spectroscopy (REELS) and angle‐dependent X‐ray absorption spectroscopy (XAS) to gain information on the films' electronic, order and interface properties. AFM studies provide valuable information on the films' nanotopographical properties and homogeneity. Spectroscopic ellipsometry and photoluminescence spectroscopy were used also to obtain information on the optoelectronic properties. Well‐ordered films were observed from the XAS analysis, measured at the sulfur K absorption edge. XPS measurements demonstrated that the surface composition of the polymer thin films prepared by a spin‐coating wet‐chemical deposition method matches the expected F8:F8BT blend stoichiometry. The interfacial properties were studied through an argon ion sputtering process coupled to the XPS acquisition, showing an enhancement of oxygen components at the interface. The films' inhomogeneity was verified by AFM images and analysis. We obtained a value of 3.1 eV as the electronic bandgap of the F8:F8BT film from REELS data, whereas analysis of the spectroscopic ellipsometry spectra revealed that the optical bandgap of F8:F8BT has a value of 2.4 eV. A strong green emission was obtained for the produced films, which is in agreement with the expected emission due to the 1:19 ratio of the F8 and F8BT blended polymers. © 2018 Society of Chemical Industry Ultrathin films of F8:F8BT poly(9,9‐di‐n‐octylfluorenyl‐2,7‐diyl) (F8) blended with poly(9,9‐dioctylfluorene‐alt‐benzothiadiazole (F8BT) were characterized by depth profiling XPS, REELS and angle‐dependent XAS.